Assessment of summer paddy water requirements: An analysis at mid plains of Chhattisgarh - KUMAR, NILESH; AGRAWAL, NARENDRA; NAIDU, DIWAKAR; JANGRE, NILIMA (Journal of Soil and Water Conservation, 2025)
Water is a crucial and finite resource, predominantly utilized for irrigation, necessitating efficient and equitable distribution for sustainability. This research quantifies the water requirements for summer paddy cultivation in the mid-plains of Chhattisgarh, based on field experiments conducted at the Department of Soil Science, Indira Gandhi Krishi Vishwavidyalaya, Raipur, and utilizing meteorological data from 1993 to 2023. The FAO-CROPWAT 8.0 model was utilized to estimate reference evapotranspiration (ET0) through the FAO Penman-Monteith method, and crop coefficient (Kc) values at different growth stages were used to compute crop evapotranspiration (ETc). A water balance model was developed in CROPWAT 8.0, incorporating region-specific soil, meteorological, and phenological factors. The analysis indicated a mean precipitation of 1244.44 mm over the 30-year period, alongside a crop water requirement (CWR) of 677.8 mm for summer paddy. The total irrigation water requirement (TIWR), after considering field losses and irrigation efficiency, was calculated to be 1002.3 mm, while the gross irrigation water requirement (GIWR) was found to be 1431.9 mm. The findings offer essential insights for sustainable agriculture and resource planning in Chhattisgarh’s mid-plains, highlighting the necessity for customized irrigation management strategies to effectively address local agricultural water demands and enhance water resource management in the context of changing climatic conditions and evolving agricultural practices.